Impact of IOT Application and Smart Cities: An analysis of the impact and trends in IoT-based smart cities (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Smart cities are made possible by the integration of IoT technology into existing urbaninfrastructure. As a result, living quality is enhanced by the efficient handling of data created by the realtimeintegration of electronic sensors. The study's primary goal is to summarise the findings of previousstudies conducted throughout the world on smart cities that make use of IoT technologies. A total of 1232papers covering the years 2011-2019 were analysed using bibliometric methods to conclude the state ofresearch on this issue and its most prevalent themes. The number of scientific papers published has beenrising steadily, with 83.23 percent of all papers being produced in the previous three years. Computerscience and engineering were the two most impressive topics. Study expansion on IoT-based smartcities has been broken down into seven distinct tracks. Also, seven potential new lines of inquiry havebeen uncovered as a result of this study. As a whole, there is a rising interest in building smart cityfeatures based on Internet of Things applications, and this interest is reflected in the world's scientificoutput. This research adds to the ongoing conversation in academic, scientific, and institutional settingson how best to use accessible data to guide policy decisions.